The effect of international work experience on the career success of expatriates: a comparison of assigned and self-initiated expatriates - Suutari, Vesa; Brewster, Chris; Mäkelä, Liisa; Dickmann, Michael; Tornikoski, Christelle (Wiley, 2017)
This paper examines the long-term effect of expatriation on careers, comparing the impact of international work experience on the career success of assigned and self-initiated expatriates. Our sample consists of employees who were working abroad in 2004 and we examine their subjective and objective career success eight years later. Despite the ‘dark side of international careers’ arguments associated with the repatriation literature, we find that the long-term impacts of international work experience on career success are generally positive and mainly unrelated to whether the work experience was acquired as an assigned or self-initiated expatriate. Companies recruit employees with international experience externally but are much more likely to offer further internal jobs to assigned expatriates. This reinforces the need for further research and for companies to see all those with international experience as important elements of the workforce.
Keywords: Careers; International work experience; Career success; Expatriates; Self-initiated expatriates